Substantial thermal conductivity reduction in mischmetal skutterudites MmxCo4Sb12 prepared under high-pressure conditions, due to uneven distribution of the rare-earth elements. Issue 14 (18th March 2019) - Gainza, J.; Serrano-Sánchez, F.; Prado-Gonjal, J.; Nemes, N. M.; Biskup, N.; Dura, O. J.; Martínez, J. L.; Fauth, F.; Alonso, J. A.
Abstract : Low-cost n-type Mischmetal-filled CoSb3 skutterudites with elemental filling-fraction separation, prepared at high pressure, exhibit markedly low lattice thermal conductivity. Abstract : Thermoelectric mischmetal-filled Mm x Co4 Sb12 (Mm: natural cocktail of rare-earth elements, mostly Ce and La) skutterudites have been synthesized and sintered in one step under high-pressure conditions at 3.5 GPa in a piston–cylinder hydrostatic press. Synchrotron X-ray diffraction patterns display a splitting of the diffraction peaks ascribed to purely Ce-, and Mm-filled skutterudite phases, which have been analyzed and confirmed by high-resolution TEM and EELS. A total thermal conductivity ( κ ) of 1.51 W m −1 K −1 is measured at 773 K for Mm0.5 Co4 Sb12, below that of other filled skutterudites, which is promoted by the enhanced phonon scattering over a broad range of the phonon spectrum due to the inhomogeneous and nanoscale mischmetal inclusion. Compared to undoped CoSb3 skutterudite synthesized by conventional methods, κ is reduced by a factor of 3, while the power factor is also substantially enhanced.